(3aYGdjI GfXeI GdJOQjH ddehGQO GdHTQjI Ydi LhOI GdNOeGJ GdJShjbjI GdebOeI dRHGFf GdeQcHGJ GdQjGVjI (B: (3OQGSI ejOGfjI cHQjGJ GdefTBJ GdQjGVjI GdLRGFQjI s - (3Hf YQhS , eMeOs; (3MOGH, Sdjes; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2021)
(3eMGhdI GdhUhd Edi eYQaI eSGgeg GdbOQGJ GdaQOjI ddYGedjf hcja jecf dge JMbjb COGA eJejR OGNd EOGQI GdehGQO GdHTQjI aj GdefTCI GdQjGVjI h eYQaI OhQ CfXeI hELQGAGJ GdYed aj JMbjb GdCOGA GdeJejR ddCaQGO(B. -(3eMGhdI GdhUhd deYQaI GdfeW GdbjGOj GdedGFe dJecjf EOGQI GdehGQO GdHTQjI ef JMbjb COGA eJejR OGNd GdefTCI GdQjGVjI(B. -(3JHjGf eOi aYGdjI GdehGQO GdHTQjI dYedjI GdLhOI GdJShjbjI OGNd GdefTBJ GdQjGVjI HGYJHGQgG GdYUH GdeMQc hGdbhI GdOGaYI ddefTCI GdQjGVjI h hVY CWQ h ejcGfjReGJ aj eLGd GdJOQjH aj eLGd GdLhOI GdNOeGJ GdJShjbjI deSGjQI GdJWhQGJ GdMGUdI hYUQfI GdefTBJ GdQjGVjI s
(3OcJhQGgs
Keywords: (3GOGQI GdehGQO GdHTQjIs; (3GdJShjb GdQjGVjs; (3JSjjQ GdehGQ O GdHTQjI GdefTCJ GdQjGVjIs